Instructional television and Nigerian students’ learning experiences: case for LASUBEB English language TV programmes - Bolajoko Margeret Tunde-Awe; Isaac Friday Emmanuel (English Language Education Study Program, Faculty of Education and Teacher Training, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, Indonesia, 2023)
With the outbreak of COVID-19 and the subsequent global lockdown, television as an educational medium became amplified for obvious reason – literacy development among children in Nigeria. This study, therefore, examined instructional TV channels and students’ learning experiences using LASUBEB English Language TV Programmes. A descriptive research design of the survey type was adopted for the study. Through simple and random sampling technique, two hundred and four (204) students were selected from the total population of 229,980 students in Lagos, Nigeria. The instrument used for this study was a self-structured questionnaire titled: TV Programmes and Students’ Learning Strategies (TVPSLS). Reliability test of r- 0.78 showed that the instrument was reliable. Three research questions were raised and answered using descriptive statistics of mean and standard deviation. The study revealed that students were not motivated to tune-in to LASUBEB TV channels; a few who tuned-in did not show any commitments to the programme and LASUBEB TV lessons did not complement what was being taught in the classrooms. This study recommends that a feedback platform should be created by TV instructional channels for assessments so that students could turn-in their end of class and end of session assignments.